Blood glucose self-monitoring in older adults: new approaches - Ilya A. Barsukov; Anna A. Demina (Клинический разбор в общей медицине)
Over the last 50 years the prevalence of Type 2 diabetes mellitus (T2DM) in older adults (>65 years) rose dramatically. Comorbidity, high risk of hypoglycemia, lack of resilience an individual care needs are additional risk factors that complicate disease management in these patients. The availability of new technologies in diabetes management allow to provide additional control of blood glucose levels in these patients by there relatives, that is of a great importance in case of frailty and dementia. As the result, the possibility of making clinical decisions based on greater amount of information allow to ameliorate not only the patient’s quality of life, but also to extend life expectancy by reducing the risk of onset and progression of macro- and microvascular complications.